The Biomechanical Characteristics of the Strongman Yoke Walk - Hindle, Benjamin R.; Lorimer, Anna; Winwood, Paul; Brimm, Daniel; Keogh, Justin W. L. (Frontiers in Sports and Active Living, 2021)
The aim of this study was to use ecologically realistic training loads and carry distances to 1) establish the preliminary biomechanical characteristics of the yoke walk; 2) determine spatiotemporal and kinematic differences between intervals of the yoke walk; and 3) identify any biomechanical differences between male and female athletes performing the yoke walk. Kinematic and spatiotemporal measures of hip and knee joint angle, and mean velocity, stride length, stride rate and stance duration of each 5 m interval were taken whilst 19 strongman athletes performed three sets of a 20 m yoke walk at 85% of their pre-determined 20 m yoke walk one repetition maximum. The yoke walk was biomechanically similar to the farmers walk (a previously researched strongman exercise) and backpack load carriage, whereby between-interval comparisons revealed increased stride length, stride rate and lower limb range of motion (ROM), and decreased stance duration at greater velocity. Although no main between-sex differences were observed, two-way interactions revealed female athletes exhibited greater knee extension at toe-off and reduced hip ROM during the initial (0 – 5 m) than the final three intervals (5 – 20 m), and covered a greater distance before reaching maximal normalised and non-normalised stride length than males. As this was the first study to assess kinematic and spatiotemporal measures of athletes performing the yoke walk, future research should assess the effect of load and anthropometrics on athlete biomechanics, as this will provide a greater understanding of possible sex-specific injury risks and biomechanical performance determinants of the yoke walk.